Rosmarinic Acid and Flavonoids of the Seagrass Zostera noltei: New Aspects on Their Quantification and Their Correlation with Sunlight Exposure - Isabel Casal-Porras; Kimberly Muñoz; María J. Ortega; Fernando G. Brun; Eva Zubía (Plants, 2023)
Seagrasses are plants adapted to the marine environment that inhabit shallow coastal waters, where they may be exposed to direct sunlight during low tides. These plants have photoprotection mechanisms, which could include the use of phenolic secondary metabolites. In this study, rosmarinic acid (RA) and the flavonoids of Zostera noltei from the Bay of Cadiz (Spain) have been analyzed, first to define suitable conditions of leaves (i.e., fresh, dried, or frozen) for quantitative analysis, and then to explore the potential correlation between the phenolic profile of the leaves and sunlight exposure using an in situ experimental approach. Compared with fresh leaves, the contents of RA and flavonoids were significantly lower in air-dried and freeze-dried leaves. Freezing caused highly variable effects on RA and did not affect to flavonoid levels. On the other hand, the content of RA was significantly higher in plants that emerged during low tides than in plants permanently submerged, while plants underneath an artificial UV filter experienced a progressive reduction in RA content. However, the major flavonoids did not show a clear response to sunlight exposure and were unresponsive to diminished UV incidence. The results showed a positive correlation of RA with direct sunlight and UV exposure of leaves, suggesting that this compound contributes to the photoprotection of Z. noltei.